Ways of Information Support of Innovative Activity of the Enterprise Improvement - Alexander Pavlovich Kovalev; Igor Mikhaylovich Levkin; Elena Yurevna Morozova (Управленческое консультирование)
In the article new approaches to information support of innovative activity of the enterprise in questions of formation and updating of databases of technical information, getting of information, competitive fight and an assessment of a demand of own scientific results are proved. Recommendations about use of methods of business investigation; to use of modern characteristics of scientific activity of experts, including the Russian index of scientific citing and Hirsh’s index; application of methods of SWOT analysis, SPACE analysis, PEST analysis, the analysis of competitors according to Porter and calculation of an integrated index of a demand of all results of research and developmental works with the third-party enterprise are made.